A Guide to Marx’s Theses on Feuerbach (World Marxist Review, 2024)
Karl Marx’s Theses on Feuerbach is, as Friedrich Engels argued, the “first document” that “deposited the brilliant germ of the new world outlook.” Its shortness and celebrated phrases have made it a classical pedagogical tool for teaching Marxism. However, with such ubiquity, this philosophically loaded text has provided fertile ground for one-sided interpretations and de-contextualized misunderstandings. To combat this, the present essay historically and philosophically elaborates on the rise of the Young Hegelians and how Marx’s Theses are situated in a broader critique of the philosophical movement he and Engels were once a part of. The essay also provides an exegesis of the Theses and incorporates critiques of the misconceptions which have arisen with the text’s popularity. In the process, the Marxist position on questions of praxis, truth, universals, human essence, and more, is set forth.